A concise review of poultry vaccination and future implementation of plant-based vaccines. Issue 3 (30th June 2017) - SHAHID, N.; RAO, A.Q.; KRISTEN, P.E.; ALI, M.A.; TABASSUM, B.; UMAR, S.; TAHIR, S.; LATIF, A.; AHAD, A.; SHAHID, A.A.; HUSNAIN, T.
Abstract : Every year the growth of the poultry industry is severely threatened by a number of infectious viral, bacterial and parasitic diseases. There are a number of vaccines to control these diseases including inactivated virus vaccines, attenuated virus vaccines, live virus vaccines, and subunit vaccines, but they are often relatively expensive and require cold storage and trained people to administer them, especially in developing countries. Plant-based vaccines provide a better option to control these diseases in low profit margin poultry industry. Still there are some challenges in the field of plant-based, so called 'green' vaccines. Injection-based oral priming is a big challenge for commercialisation of green vaccines so, new techniques are needed in the field of plant-based vaccine to pass these barriers for commercialisation. This discusses the potential for plant-based vaccines and whether they are good option to control poultry diseases.